On the Paramount Role of Absorber Stoichiometry in (Ag, Cu)(In, Ga)Se2 Wide‐Gap Solar Cells. Issue 12 (29th September 2020) - Keller, Jan; Stolt, Lars; Sopiha, Kostiantyn V.; Larsen, Jes K.; Riekehr, Lars; Edoff, Marika
Abstract : This contribution evaluates the effect of absorber off‐stoichiometry in wide‐gap (Ag, Cu)(In, Ga)Se2 (ACIGS) solar cells. It is found that ACIGS films show an increased tendency to form ordered vacancy compounds (OVCs) with increasing Ga and Ag contents. Very little tolerance to off‐stoichiometry is detected for absorber compositions giving the desired properties of 1) an optimum bandgap ( E G ) for a top cell in tandem devices ( E G = 1.6–1.7 eV) and at the same time 2) a favorable band alignment with a CdS buffer layer. Herein, massive formation of either In‐ or Ga‐enriched OVC patches is found for group I‐poor ACIGS. As a consequence, carrier transport and charge collection are significantly impeded in corresponding solar cells. The transport barrier appears to be increasing with storage time, questioning the long‐term stability of wide‐gap ACIGS solar cells. Furthermore, the efficiency of samples with very high Ga and Ag contents depends on the voltage sweep direction. It is proposed that the hysteresis behavior is caused by a redistribution of mobile Na ions in the 1:1:2 absorber lattice upon voltage bias. Finally, a broader perspective on OVC formation in the ACIGS system is provided and fundamental limitations for wide‐gap ACIGS solar cells are discussed. Abstract : Very low tolerance to off‐stoichiometry is detected for wide‐gap ( E G > 1.6 eV) (Ag, Cu)(In, Ga)Se2 (ACIGS) solar absorbers. Substantial formation of ordered vacancy compounds for group I‐poor ACIGS correlates with a deteriorated solar cell performance and long‐term degradation. Substitution of CdS by an alternative buffer is suggested to allow for greater flexibility in absorber composition.